Analisis Kepuasan Pengguna E-Commerce terhadap Tingkat Loyalitas : Analysis of E-Commerce User Satisfaction on Student Loyalty Level - Muhammad Ghazi Raiqal (Asosiasi Ahli Administrasi Indonesia, 2022)
This study examines the relationship between e-commerce user satisfaction and the level of loyalty among Business Administration students at Bandung, Indonesia. Involving 100 respondents, the research employed a questionnaire to gather demographic data and variables related to user satisfaction and consumer loyalty. The results of the demographic analysis show a balanced distribution of respondents across various academic levels, study programs, genders, and income levels. The validity and reliability tests of the measurement instrument indicate that the research instrument is valid and reliable. Simple regression analysis yielded a coefficient of determination of 26%, indicating that e-commerce user satisfaction has a positive influence on student loyalty. The study provides insights into the factors influencing purchasing decisions among students and suggests enhanced marketing strategies to improve user satisfaction.